A Conserved Role for the NAM/miR164 Developmental Module Reveals a Common Mechanism Underlying Carpel Margin Fusion in Monocarpous and Syncarpous Eurosids - Vialette-Guiraud, Aurélie C. M.; Chauvet, Aurélie; Gutierrez-Mazariegos, Juliana; Eschstruth, Alexis; Ratet, Pascal; Scutt, Charles P. (Frontiers in Plant Science, 2016)
The majority of angiosperms are syncarpous- their gynoecium is composed of two or more fused carpels. In Arabidopsis thaliana, this fusion is regulated through the balance of expression between CUP SHAPED COTYLEDON (CUC) genes, which are orthologues of the Petunia hybrida transcription factor NO APICAL MERISTEM (NAM), and their post-transcriptional regulator miR164. Accordingly, the expression of a miR164-insensitive form of Ar. thaliana CUC2 causes a radical breakdown of carpel fusion. Here, we investigate the role of the NAM/miR164 genetic module in carpel closure in monocarpous plants. We show that the disruption of this module in monocarpous flowers of Ar. thaliana aux1-22 mutants causes a failure of carpel closure, similar to the failure of carpel fusion observed in the wild-type genetic background. This observation suggested that closely related mechanisms may bring about carpel closure and carpel fusion, at least in Ar. thaliana. We therefore tested whether these mechanisms were conserved in a eurosid species that is monocarpous in its wild-type form. We observed that expression of MtNAM, the NAM ortholog in the monocarpous eurosid Medicago truncatula, decreases during carpel margin fusion, suggesting a role for the NAM/miR164 module in this process. We transformed M. truncatula with a miR164-resistant form of MtNAM and observed, among other phenotypes, incomplete carpel closure in the resulting transformants. These data confirm the underlying mechanistic similarity between carpel closure and carpel fusion which we observed in Ar. thaliana. Our observations suggest that the role of the NAM/miR164 module in the fusion of carpel margins has been conserved at least since the most recent common ancestor of the eurosid clade, and open the possibility that a similar mechanism may have been responsible for carpel closure at much earlier stages of angiosperm evolution. We combine our results with studies of early-diverging angiosperms to speculate on the role of the NAM/miR164 module in the origin and further evolution of the angiosperm carpel.